A rare presentation of a middle ear osteoma of the incus case report - Kiran Jumani; Miljyot Singh Sangha; Ashok Adams; Delisha Naaz; Victoria Bryant (Acta Oto-Laryngologica Case Reports)
Middle ear osteoid osteomas are rare, and they can be misdiagnosed as otosclerosis. Conductive hearing loss, aural fullness, tinnitus and rarely otorrhoea are presenting symptoms. A rare paediatric case is highlighted here. The aim is to consider this amongst differential diagnosis and the operative technique has also been discussed. A 10-year-old girl with a one-year history of intermittent bloody otorrhoea presented to the Whipps Cross paediatric otology clinic. CT and MRI scan demonstrated an intrinsic lesion centred on the incus. Otoendoscopic examination and radiological investigations deemed the lesion of undetermined significance. A transcanal endoscopic excision of this lesion was performed. Histology revealed a lesion consistent with an osteoid osteoma. Osteoid osteomas of the middle ear represent an important differential diagnosis to consider when assessing patients with otalgia, otorrhea, tinnitus and an associated conductive deafness.